Monogenic susceptibility to live viral vaccines. (October 2021) - Gothe, Florian; Howarth, Sophie; Duncan, Christopher JA; Hambleton, Sophie
Abstract : Live attenuated viral vaccines (LAV) have saved millions of lives globally through their capacity to elicit strong, cross-reactive and enduring adaptive immune responses. However, LAV can also act as a Trojan horse to reveal inborn errors of immunity, thereby highlighting important protective elements of the healthy antiviral immune response. In the following article, we draw out these lessons by reviewing the spectrum of LAV-associated disease reported in a variety of inborn errors of immunity. We note the contrast between adaptive disorders, which predispose to both LAV and their wild type counterparts, and defects of innate immunity in which parenterally delivered LAV behave in a particularly threatening manner. Recognition of the underlying pathomechanisms can inform our approach to disease management and vaccination in a wider group of individuals, including those receiving immunomodulators that impact the relevant pathways.